Analisis Perilaku Konsumen dalam Pembelian Daging Ayam Ras Pedaging Di Pasar Tradisional Amuntai - Purna Kusumayana; Selvia Seftiani (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
This study aimed to identify the characteristics of consumers and analyze the factors that influence consumer behavior in buying broiler meat in the traditional market Amuntai. Methods of data collection by direct interview method to consumers who buy broiler meat. Data collection was done by accidental sampling method who met the broiler meat consumers, with 75 respondents. Based on the result of research, it is known that the dominant consumer characteristic is female gender 64 people (85,3%), age 41-50 years 33 people (44%), high school education level 34 people (45,3%), households 28 people (37.3%), with income Rp. 1,000,000 - Rp. 2,000,000 25 people 933.3%). Regression analysis results obtained value of coefficient of determination (R2) of 0, 458 or 45.8% there is the influence of independent variables include cultural, social, personal, and psychological to purchase decisions, while 54.2% influenced by other factors not included in the regression model From the results of regression testing as follows: Y = 5,633 + 0,421 X1 - 0,208 X2 + 0,055 X3 + 0,300 X4. Simultaneously independent variables include cultural, social, personal, and psychological significant effect on purchasing decisions. Partially cultural, social and psychological factors significantly affect purchasing decisions while personal factors have no significant effect on purchasing decisions